2019
DOI: 10.4103/lungindia.lungindia_475_18
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome of multidrug-resistant tuberculosis with modified DOTS-plus strategy: A 2 years' experience

Abstract: Background: Multidrug-resistant tuberculosis (MDR-TB) is a global health problem with notoriously difficult and challenging treatment. This study determined treatment outcome in patients of MDR-TB with modified DOTS-Plus strategy. Methods: Ninety-eight consecutive MDR-TB patients treated with standardized regimen according to modified DOTS-Plus strategy aligned to the existing national DOTS-Plus guidelines with relevant modifications proposed by Chennai consensus were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
3
8
0
Order By: Relevance
“…Singh et al in their study found Unilateral in 5(5.1%) cases and Bilateral in 93(94.9%) cases, however he reported most common finding was consolidation 70(71.4%) in his study. 9 In the present study, out of 93 patients, sputum microscopy conversion was 87.1% (n=81/93), 95.7% (n=89/93), 98.9% (n=92/93), 100% (n=93/93) at 3-month, 4-month, 5 month, and 6 month respectively. While culture conversion at 3 month was 95.7% (n=89/93).…”
Section: Discussionsupporting
confidence: 43%
See 4 more Smart Citations
“…Singh et al in their study found Unilateral in 5(5.1%) cases and Bilateral in 93(94.9%) cases, however he reported most common finding was consolidation 70(71.4%) in his study. 9 In the present study, out of 93 patients, sputum microscopy conversion was 87.1% (n=81/93), 95.7% (n=89/93), 98.9% (n=92/93), 100% (n=93/93) at 3-month, 4-month, 5 month, and 6 month respectively. While culture conversion at 3 month was 95.7% (n=89/93).…”
Section: Discussionsupporting
confidence: 43%
“…The association between treatment outcome and age group, gender were not significant (P=0.113, 0.323 respectively), similar observation reported by other previous studies. 8,9 In the present study, 66(71%) patients had BMI <18.5kg/m 2 while 27(29%) had BMI 18.5-24.9kg/m 2 . Mean BMI was 17.3±2.1 (range=12.…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations